IS THERE AN ALTERNATIVE TO EJECTION FRACTION IN INSTRUMENTAL EVALUATION OF CHRONIC HEART FAILURE SEVERITY IN POST-MYOCARDIAL INFARCTION PATIENTS? - T. A. Kazakovtseva; N. A. Shostak (Столичная издательская компания, 2016)
Aim. To find echocardiographic indicators of the heart remodeling which provide the best evaluation of chronic heart failure (CHF) severity in post-myocardial infarction patients.Material and methods. Patients (n=100) with CHF related with ischemic heart disease (post-myocardial infarction) have been examined. The CHF severity was assessed by Scale of Clinical State Evaluation (SCSE) in V.Yu. Mareev's modification and 6-minute walk test. The echocardiography was performed with registration of the heart cavities size, left ventricle (LV) myocardium mass, LV asynergy index, LV sphericity index, time of LV isovolumic contraction and relaxation, Е/А ratio for mitral flow, grade of valvular regurgitation and pulmonary hypertension.Results. The maximal correlation values of CHF severity was observed with intensity of diastolic dysfunction, systolic LV size and volume, LV asynergia index, integrated systolic remodeling index, degree of mitral regurgitation. Correlation value of CHF severity with LV ejection fraction was less than this with above mentioned indices.Conclusion. The early echocardiographic markers of CHF were found. These are LV systolic sphericity index, LV integrated systolic remodeling index, LV systolic myocardial stress.